Stage IV Burkitt Lymphoma Presenting with Eyelid Swelling - Chong, Soh Yee; Ho, Shu Fen; ST, Khairy-Shamel (IIUM Medical Journal Malaysia, 2019)
Burkitt lymphoma is a rare and aggressive tumour which predominantly affects children. We report a case of Stage IV Burkitt lymphoma (non-endemic type) in a 5-year-old immunocompetent Malay child who initially presented with left upper eyelid swelling. Clinical examination revealed a soft solid swelling over the left upper lid, extending temporally up to the lacrimal gland. Computed tomography (CT) scan showed a homogenous mass of soft tissue density with intracranial and left orbital involvement. Incisional biopsy of the mass revealed histological changes suggestive of B lymphoblastic lymphoma or leukemia. She was treated with 6 cycles of chemotherapy. Post chemotherapy, the left temporal and upper eye lid swelling subsided. Clinicians need to be on alert when encountering children with eyelid swelling, as this could be an initial presenting feature of Burkitt lymphoma without other systemic symptoms. A delay in diagnosis can lead to aggressive orbital involvement followed by permanent visual loss.